Bring 'Em On: Media and Politics in the Iraq War - Kamalipour, Yahya R.; Artz, Lee (Rowman & Littlefield Publishers, 2004)
How were the American people prepared for the war on Iraq? How have political agents and media gatekeepers sought to develop public support for the first preventive war of the modern age? Bring 'Em On highlights the complex links between media and politics, analyzing how communication practices are modified in times of crisis to protect political interests or implement political goals. International contributors in mass communication, political science, and sociology address how U.S. institutional media practices, government policy, and culture can influence public mobilization for war.